1996
DOI: 10.1046/j.1365-2818.1996.72348.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative atomic force and scanning electron microscopy: an investigation on fenestrated endothelial cells in vitro

Abstract: SummaryRat liver sinusoidal endothelial cells (LEC) contain fenestrae, which are clustered in sieve plates. Fenestrae control the exchange of fluids, solutes and particles between the sinusoidal blood and the space of Disse, which at its back side is flanked by the microvillous surface of the parenchymal cells. The surface of LEC can optimally be imaged by scanning electron microscopy (SEM), and SEM images can be used to study dynamic changes in fenestrae by comparing fixed specimens subjected to different exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
2
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 31 publications
2
47
2
1
Order By: Relevance
“…The potent effect of microfilament disassembly on fenestra induction in bEND5 cells and the spatial and temporal correlation between stress fiber disassembly and sieve plate formation highlighted the importance of actin microfilaments. Whereas previous studies had addressed the role of actin disassembly in sustaining or modulating the number of pores in fenestrated liver endothelial cells (31)(32)(33)35) and isolated kidney glomeruli (36), we demonstrated a role for actin disassembly in de novo fenestra formation. Our observations of a rearrangement of large actin filaments during fenestra induction by the physiological stimulus VEGF and the prevention of such rearrangements and fenestra induction by the F-actin-stabilizing drug phalloidin further supported a role for actin remodeling in fenestra formation.…”
Section: Discussioncontrasting
confidence: 61%
“…The potent effect of microfilament disassembly on fenestra induction in bEND5 cells and the spatial and temporal correlation between stress fiber disassembly and sieve plate formation highlighted the importance of actin microfilaments. Whereas previous studies had addressed the role of actin disassembly in sustaining or modulating the number of pores in fenestrated liver endothelial cells (31)(32)(33)35) and isolated kidney glomeruli (36), we demonstrated a role for actin disassembly in de novo fenestra formation. Our observations of a rearrangement of large actin filaments during fenestra induction by the physiological stimulus VEGF and the prevention of such rearrangements and fenestra induction by the F-actin-stabilizing drug phalloidin further supported a role for actin remodeling in fenestra formation.…”
Section: Discussioncontrasting
confidence: 61%
“…However, latrunculin A increases the number of fenestrae more rapidly than cytochareports confirmed the increase in the number of fenestrae when LECs were treated with cytochalasin B. 8,[17][18][19][20][21][22][23] lasin B (Fig. 2).…”
Section: Ultrastructuralmentioning
confidence: 87%
“…After 1 hour of treatment, an equal maximum ous experimental conditions. 8,[19][20][21][22][23] The conclusion is allowed number of fenestrae was observed for both agents. The that a change in the number of fenestrae depends on the effect of latrunculin A was obtained at concentrations state of polymerization of the actin cytoskeleton.…”
mentioning
confidence: 99%
“…At present, there are three main techniques to study the cellular cytoskeleton: TEM [1,2], immunofluorescence microscopy [3,4], and developed recently, transmission X-ray microscopy [5]. It was found that the cytoskeleton consists of three types of filaments: microtubules, microfilaments, and intermediate filaments.…”
Section: Introductionmentioning
confidence: 99%